2017
DOI: 10.1111/zph.12346
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for exposure to avian influenza viruses within poultry workers in southern China

Abstract: The risk of infection with avian influenza viruses for poultry workers is relatively unknown in China, and study results are often biased by the notification of only the severe human cases. Protein microarray was used to detect binding antibodies to 13 different haemagglutinin (HA1-part) antigens of avian influenza A(H5N1), A(H7N7), A(H7N9) and A(H9N2) viruses, in serum samples from poultry workers and healthy blood donors collected in the course of 3 years in Guangdong Province, China. Significantly higher an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…However, challenges remain and efforts toward a One Health approach should be continued. Serosurveys in epidemiologic studies to follow up exposed cohorts and identify possible transmission events might better describe the risk for transmission and help reduce uncertainty when assessing the risk for those newly emerging viruses, despite known limitations regarding subtype specificity of serologic testing ( 33 , 34 ). Despite a wide diversity in the recommendations for use of PPE and of antiviral prophylaxis for exposed persons, we found no evidence of bird-to-human transmission of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, challenges remain and efforts toward a One Health approach should be continued. Serosurveys in epidemiologic studies to follow up exposed cohorts and identify possible transmission events might better describe the risk for transmission and help reduce uncertainty when assessing the risk for those newly emerging viruses, despite known limitations regarding subtype specificity of serologic testing ( 33 , 34 ). Despite a wide diversity in the recommendations for use of PPE and of antiviral prophylaxis for exposed persons, we found no evidence of bird-to-human transmission of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, 32 human cases of infection caused by the H9N2 G1 lineage but not by the other lineages have been reported, with cases being reported from China (n ϭ 25), Bangladesh (n ϭ 3), and Egypt (n ϭ 4) (14). Recent serology data suggested that the incidence of exposure to and possible infection with H9N2 G1-like viruses in humans may be considerably underestimated (15,16). Unlike infection with gs/GD H5 or H7N9 viruses, most of the reported cases of human H9N2 infection developed mild signs of disease, and no evidence of human-to-human transmission has been recorded (17,18).…”
mentioning
confidence: 99%
“…Similar variability on the seropositivity rates were found among poultry workers that were exposed to avian influenza viruses in other studies, ranging from 0.4% to 56% among poultry workers [17][18][19][20] . Recently, we developed protein array (PA) based serological assays to profile antibody responses to a range of influenza virus HA1 antigens, in an attempt to obtain a more granular analysis of the antibody responses in individuals exposed to human and animal influenza viruses [21][22][23] . While this showed the ability to measure subtype specific antibodies, the diverse reactivity of antibodies in serum samples from adults with a history of multiple influenza virus infections makes it challenging to conclude on exposure history from serum profiling.…”
mentioning
confidence: 99%